TerraSAR-X observations of the northeastern Adriatic bora: Early results Opažanja sjeveroistočno-jadranske bure pomoću satelita TerraSAR-X: Rani rezultati - Kuzmić, Milivoj; Li, Xiao Ming; Grisogono, Branko; Tomažić, Igor; Lehner, Susanne (Acta Adriatica, 2013)
Some early results of the TerraSAR-X observations of the northeastern Adriatic bora wind are presented in this paper. TerraSAR-X is a German X-band radar satellite launched in 2007 that carries phased array X-band synthetic aperture radar (SAR) operating in different polarizations and providing multiple imaging modes. SAR backscatter can be used to derive wind fields at spatial resolution that no other instrument can provide. Terrain-induced jet and wake patterns are particularly conductive to the SAR-instrument examination. Bora, a cold and dry downslope wind blowing from north-easterly directions on the eastern side of the Adriatic Sea, exhibits such a response. Since bora is primarily winter wind and the town of Senj is known for frequent and severe bora episodes we focus on TerraSAR-X scenes collected in the winters of 2011 and 2012 over an area with Senj roughly in its center. Recently developed XMOD2 geophysical model function is used for wind magnitude derivation, whereas the WRF model was employed to estimate the wind direction. The selected TerraSAR-X scenes have captured representative bora events exhibiting rich details in bora-induced jet and wake patterns on the lee of the Dinaric Alps. The details registered in the normalized radar cross section response strongly suggest the need for still higher resolution numerical simulations in order to properly model the orographic impact on and the fine details in the surface wind field. Comparisons with both research and operational modeling results indicate that the currently used geophysical model function may benefit from enlarging the matchup data base with samples of severe winds.
CRIS-Team Scopus Importer:2024-03-18
Keywords: Adriatic; Bora wind; TerraSAR-X